ANALYSIS OF SMART URBAN GOVERNANCE FROM THE PERSPECTIVE OF DYNAMIC GOVERNANCE IN THE CITY OF SURABAYA - Berliana Mustika Rani; Grace Carolina Malau (Politeknik STIA LAN Makassar, 2025)
The transformation of urban governance toward smart governance has become a strategic agenda for building responsive, transparent, and inclusive cities. Surabaya, as one of Indonesia’s leading smart cities, has demonstrated various digital innovations that require in-depth analysis from an institutional and adaptive governance perspective. This study aims to analyze the implementation of Smart Urban Governance in Surabaya using the Dynamic Governance framework, which emphasizes the principles of Thinking Ahead, Thinking Again, and Thinking Across. A qualitative research approach was employed, utilizing in-depth interviews, field observations, and document analysis. The study examined seven key indicators of smart governance: inclusiveness, responsiveness, transparency and accountability, data governance, collaborative governance, digital infrastructure and capacity, and institutional adaptability. The findings reveal that Surabaya has successfully implemented most of these indicators through various innovations such as the WargaKu application, e-Peken platform, Command Center 112, and a paperless bureaucracy system. However, challenges remain in ensuring the inclusion of vulnerable groups and in addressing complex complaints across sectors. The study concludes that the principles of Dynamic Governance are reflected in Surabaya’s digital policies, although improvements are still needed in citizen participation and cross-sectoral integration. This research recommends expanding digital literacy, conducting continuous evaluations of digital platform performance, and undertaking comparative studies with other cities to strengthen smart governance policies in Indonesia.